Development of Internal Supervisory Manual for Small Schools Under Chumphon Primary Educational Service Area Office 2 - Suwannarat, Sunisa; Sangkhaosuthirak, Sathaporn; Jaroensuk, Bunjong (Rajapark Journal, 2022)
The objectives of this study were: 1) to study the problems of internal supervision; 2) to develop the internal supervisory manual; and 3) to assess the suitability, feasibility, and usefulness of the internal supervisory manual for small schools under the Chumphon Primary Educational Service Area Office 2. This study was conducted using a research and development methodology. The research procedure consisted of three steps as follows: Step 1 was used to study the problems of internal supervision. Data were collected from 132 participants, including school administrators, heads of academic affairs, and teachers responsible for internal quality assurance in small schools by questionnaire; Step 2 was used to develop the internal supervisory manual, which accuracy and completeness of the manual were evaluated by eight experts; and Step 3 was used to assess the suitability, feasibility, and usefulness of the internal supervisory manual for small schools. Data were collected from a sample group of 56 small school administrators by the assessment form for suitability, feasibility, and usefulness. The data were analyzed by percentage, mean, and standard deviation. The research findings were as follows. 1) The overall problems of internal supervision of small schools were at a high level ranked. 2) The internal supervisory manual consisted of four parts: (1) Introduction, (2) Roles and duties, (3) Internal supervision process, and (4) Guidelines for internal supervisory operation. 3) The overall assessment of the suitability, feasibility, and usefulness of the internal supervisory manual for small schools was at a high level ranked.